2005
DOI: 10.1038/sj.cgt.7700921
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral injection of adenovirus vector expressing NK4 combined with gemcitabine treatment suppresses growth and metastasis of human pancreatic cancer cells implanted orthotopically in nude mice and prolongs survival

Abstract: NK4 or adenovirus vector expressing NK4 (Ad-NK4) can act bifunctionally as a hepatocyte growth factor antagonist and angiogenesis inhibitor and has potential value in cancer therapy. The aim of this study was to evaluate the therapeutic efficacy of Ad-NK4 in combination with gemcitabine (GEM) against pancreatic cancer. In vitro study showed a strong antiproliferative effect of GEM and a potent anti-invasive effect of Ad-NK4 against pancreatic cancer cells. In in vivo experiments, SUIT-2 human pancreatic cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…We earlier reported that Ad-NK4 combined with GEM suppressed the growth and metastasis of human pancreatic cancer cells implanted orthotopically into nude mice. 11 In the study, we did not examine the detailed mechanism of the enhanced suppression of tumor growth and metastasis, because we considered that the suppression effect of the combination therapy was simply induced by the combined effects of GEM-mediated growth inhibition and NK4-mediated invasion inhibition. However, our earlier data also revealed remarkable inhibitory effects on the invasive potential of cells, such as tumor invasive growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We earlier reported that Ad-NK4 combined with GEM suppressed the growth and metastasis of human pancreatic cancer cells implanted orthotopically into nude mice. 11 In the study, we did not examine the detailed mechanism of the enhanced suppression of tumor growth and metastasis, because we considered that the suppression effect of the combination therapy was simply induced by the combined effects of GEM-mediated growth inhibition and NK4-mediated invasion inhibition. However, our earlier data also revealed remarkable inhibitory effects on the invasive potential of cells, such as tumor invasive growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…We earlier showed that peritumoral injection of Ad-NK4 combined with GEM suppressed the growth of pancreatic cancer cells implanted orthotopically into nude mice, 11 but did not examine the effects of GEM on the expression levels of NK4 in vivo. Therefore, we investigated whether the enhanced effects of the combination therapy were partly due to increased levels of NK4 expression within the tumors.…”
Section: Gem and Ad Gene Therapy For Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report has shown that introduction of a fusion gene combining deoxycytidine kinase and uridine monophosphate kinase, which convert gemcitabine into its toxic phosphorylated metabolite, sensitizes pancreatic cancer cells to gemcitabine by reducing dramatically both in vitro cell viability and in vivo tumor volume (Vernejoul et al, 2006). Moreover, the combinations of gemcitabine treatment with introduction of IFN-α, NK4, or p53 significantly suppress the growth and the metastasis of human pancreatic cancer cells, suggesting the enhancement of chemotherapy by gene therapy approach in pancreatic cancer (Bhattacharyya and Lemoine, 2006;Ogura et al, 2006). Collectively, the brief information presented in this article provides state-of-the art knowledge toward new and novel therapies for pancreatic cancer and as such must be tested in human patients.…”
Section: Using Gene Therapy To Enhance Cancer Chemotherapeutic Efficacymentioning
confidence: 99%
“…Therefore, molecular therapies for pancreatic cancer are promising new approaches to treat this often fatal disease. Investigators have used adenovirus-mediated gene transfer to treat pancreatic cancer and reported that adenovirus-mediated gene therapy inhibited progression of pancreatic cancer in vivo and in vitro (17,18). However, clinical trials revealed that it is difficult to eradicate pancreatic tumors with adenovirusmediated gene therapy alone (19,20).…”
mentioning
confidence: 99%